KOMPENSASI KINERJA BERBASIS MOTIVASI PEGAWAI DI RUMAH SAKIT AL-ARIF KABUPATEN CIAMIS - Fachmi Syam Arifin; Rindu Garvera; Jaka Nur (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
The low performance of employees is not only influenced by career development and compensation from the company, one of which is the work motivation factor for most employees, where employees still do not feel motivated by what they have obtained while carrying out their duties as employees. Performance compensation based on employee motivation will have an impact on service satisfaction and has an important role in improving employee performance. The research method used is descriptive qualitative method. The calculation of absenteeism as the effect of performance-based compensation on employee motivation is measured from the list of employee attendance and absences or absenteeism conducted at Al Arif Hospital, Ciamis district.